Cyberbullying: the new work risk in virtuality - González Celin, Yuranis Selene (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
The objective of this article is to show how workplace harassment has become relevant with the growing adoption of remote work and how a lack of physical interaction can amplify tensions, misunderstandings and conflicts, giving rise to harassment situations that negatively affect the well-being and performance of employees. workers. This type of harassment can manifest itself in various forms, such as excessive monitoring, deliberate exclusion, intimidation through messages or calls, or the spread of rumors or false information, all resulting in a bad work environment, poor performance and negative emotional state. This is why it is essential to encourage open communication between all members of the organization, stay informed, raise awareness, provide emotional support and resources for mental health, and promote a healthy balance between work and personal life. You can also establish clear guidelines on the use of online communication and collaboration tools to avoid abuse and misunderstandings. It must be taken into account that whether violence is physical or digital, it is detrimental to the work environment since it affects both employees and the goals and objectives of the entity.